2011
DOI: 10.1074/jbc.m111.237685
|View full text |Cite
|
Sign up to set email alerts
|

Mutant TRPV4-mediated Toxicity Is Linked to Increased Constitutive Function in Axonal Neuropathies

Abstract: Mutations in TRPV4 have been linked to three distinct axonal neuropathies. However, the pathogenic mechanism underlying these disorders remains unclear. Both gain and loss of calcium channel activity of the mutant TRPV4 have been suggested. Here, we show that the three previously reported TRPV4 mutant channels have a physiological localization and display an increased calcium channel activity, leading to increased cytotoxicity in three different cell types. Patch clamp experiments showed that cells expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 24 publications
3
40
0
1
Order By: Relevance
“…Intracellular Ca 2 þ signals are crucial for diverse cellular processes such as survival and death; therefore, cells expressing the TRPV4 mutants might struggle to maintain [Ca 2 þ ] i at non-toxic levels. Indeed, propidium iodide uptake experiments revealed that the expression of the N296D-H299P mutant, as well as the R269H and R315W mutants 9,10 , caused a marked increase in cell death (Fig. 8c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular Ca 2 þ signals are crucial for diverse cellular processes such as survival and death; therefore, cells expressing the TRPV4 mutants might struggle to maintain [Ca 2 þ ] i at non-toxic levels. Indeed, propidium iodide uptake experiments revealed that the expression of the N296D-H299P mutant, as well as the R269H and R315W mutants 9,10 , caused a marked increase in cell death (Fig. 8c).…”
Section: Resultsmentioning
confidence: 99%
“…The mutations in TRPV4 are the most recently identified CMT subtype, in terms of genetic locus 1,2 . Previous studies have suggested that the gain-of-function mutations of TRPV4 in these diseases, which exhibit increased basal and maximum Ca 2 þ channel activities, are clustered within the TRPV4 ARD and affect arginine residues, especially at the R232C, R269C/H, R315W, R316C/H positions [7][8][9][10] . The increased Ca 2 þ influx and subsequent Ca 2 þ overload associated with these mutations are thought to be the cause of cell death, and have been proposed as a mechanism for peripheral axonal degeneration in TRPV4-dependent neuropathies 9,10 .…”
mentioning
confidence: 99%
“…The calculation was performed using a T of 3 ms (Fecto et al, 2011), V of 10 fl, a volume similar to that occupied by a Ca 2+ spark in the absence of EGTA (Cheng et al, 1993;Nelson et al, 1995), and B of 80 (Guerrero et al, 1994). With these conditions, a Ca 2+ flux of 1.3 × 10 17 mol/s (equivalent to a current of 2.5 pA) would produce a [Ca 2+ ] i of 50 nM.…”
Section: Discussionmentioning
confidence: 99%
“…Gain-of-function mutants such as R269H and R316C elicit increased current responses to TRPV4 agonists as well as Ca 2ϩ loading to cells. These Ca 2ϩ overloads caused by constitutive activities of TRPV4 mutants are believed to be a leading cause of neurodegeneration of peripheral nerves (6,9). Although the association between TRPV4 mutation and motor/sensory neuropathies has been clearly established, the physiological function of TRPV4 in sensory and motor neurons in the normal condition remains unknown.…”
mentioning
confidence: 99%
“…Recent genetic linkage studies in patients indicate that mutations in the ankyrin repeat domains of TRPV4 are implicated in the neuropathies (5)(6)(7)(8). The gain-of-function mutations in the ankyrin repeat domain of TRPV4 are known to cause degenerative diseases involving peripheral nerves (6,7,9). Gain-of-function mutants such as R269H and R316C elicit increased current responses to TRPV4 agonists as well as Ca 2ϩ loading to cells.…”
mentioning
confidence: 99%